2018
DOI: 10.2147/cia.s163467
|View full text |Cite
|
Sign up to set email alerts
|

The effect of positive changes during intraoperative monitoring of the functional improvement in patients with cervical compressive myelopathy

Abstract: BackgroundCervical compressive myelopathy (CCM) is a progressive, degenerative spine disease and the most common cause of spinal cord dysfunction in older individuals. Current clinical guidelines for spinal surgery recommend multimodal intraoperative monitoring (IOM) during spinal surgery as a reliable and valid diagnostic adjunct to assess spinal cord integrity. The aim of this study was to evaluate the effect of positive changes during IOM on the functional status in patients with CCM.MethodsPatients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
(36 reference statements)
0
11
2
2
Order By: Relevance
“…MEPI was evident in more than 50% of the patients undergoing surgery, in contrast to previous studies 11,12 finding much smaller proportions. However, direct comparisons with those studies might not be possible since the cortical stimulation parameters were not reported.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…MEPI was evident in more than 50% of the patients undergoing surgery, in contrast to previous studies 11,12 finding much smaller proportions. However, direct comparisons with those studies might not be possible since the cortical stimulation parameters were not reported.…”
Section: Discussioncontrasting
confidence: 98%
“…21 However, these findings are not based on IOM data. Two previous studies 11,12 produced different results, correlating MEP improvement with better outcomes at 6 months and 1 month. However, the stimulation protocols were not stated explicitly and are actually unlikely to be comparable between the two studies, and their outcome measures were also dissimilar.…”
Section: Jcnmentioning
confidence: 91%
See 1 more Smart Citation
“…Some controversy remains about the overall efficacy of surgery for cervical myelopathy [ 7 , 14 ] although recent data have associated IONM with postoperative clinical outcome benefits [ 1 , 16 , 29 ]. Further research that utilizes larger samples, comparable and efficient stimulation protocols, and standardized outcome measures for longer follow-up periods may shed some light on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…Positive changes in MEP during monitoring may reflect a functional improvement 1 month after surgery in CSM patients [61]. However, the neuropathic pain and long-term functional outcomes are not affected.…”
Section: Diagnostic Tests For Csmmentioning
confidence: 99%